Arduino for beginners : complete course. (Manning Publications, 2022)
When I look at the online resources to learn Arduino, I see many tutorials and courses that only explain the result of a project. These courses focus on making you run a project as quickly as possible to make you feel that you've made great progress. The reality is that you've just scratched the surface, then good luck with creating a new project on your own. Current resources don't cover the basics, nor do they discuss advanced or unrelated hardware concepts, and don't offer a hands-on demonstration of how Arduino works. I've created this course so you can really understand what you're doing. You can start from scratch and get the necessary foundation you need, learning the complete process to create Arduino projects through practice and hands-on lessons. I'm not just teaching Arduino without real-world experience with it. As an example, a few years ago I used the Arduino environment to create a complete 6-axis robotic arm, now sold in the market. This was a real challenge and made me develop a practical mindset as well as understand what is important to learn and in what order. This course is the result of many years of learning, practice, development of real commercial products, and teaching. At the end of this course, you will have a strong Arduino foundation, and you will be able to start any custom Arduino project you want.